2015
DOI: 10.1021/acs.jpcb.5b10189
|View full text |Cite
|
Sign up to set email alerts
|

Angular Scattering Dynamics of the CH4 + Cl → CH3 + HCl Reaction Using Nearside–Farside, Local Angular Momentum, and Resummation Theories

Abstract: The differential cross section (DCS) for the CH4 + Cl → CH3 + HCl reaction is studied at six total energies where all of the species are in their ground states. The scattering (S) matrix elements have been calculated by the rotating line umbrella method for a dual-level ab initio analytic potential energy surface. We make the first application to this reaction of nearside-farside (NF) and local angular momentum (LAM) techniques, including resummation orders (r) of 0, 1, 2, and 3 for the partial-wave series rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…The Cl + CH 4 →HCl + CH 3 reaction has been the subject of extensive experimental and theoretical investigations due to its crucial role in the Cl/O 3 destruction chain mechanism in the stratosphere, and has become a prototype for studying mode specificity and bond selectivity in polyatomic reactions with a late barrier (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). As a hydrogen transfer reaction between the heavy Cl atom and relatively heavy CH 3 moieties, it is also an ideal HLH system for dynamics study.…”
mentioning
confidence: 99%
“…The Cl + CH 4 →HCl + CH 3 reaction has been the subject of extensive experimental and theoretical investigations due to its crucial role in the Cl/O 3 destruction chain mechanism in the stratosphere, and has become a prototype for studying mode specificity and bond selectivity in polyatomic reactions with a late barrier (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). As a hydrogen transfer reaction between the heavy Cl atom and relatively heavy CH 3 moieties, it is also an ideal HLH system for dynamics study.…”
mentioning
confidence: 99%
“…In addition, our theoretical development applies to reactions treated by many other approximate theoretical techniques such as reduced dimensionality methods [17,18], e.g. the rotating-line-umbrella approximation for reactions of the type…”
Section:  mentioning
confidence: 99%
“…Now, there is no guarantee that the NF decomposition ()–() is physically meaningful, even though it is mathematically exact. However, it is known that a resummation of the PWS () can significantly improve the physical effectiveness of a NF decomposition, a process known as “cleaning”. ,, ,,, A detailed account of resummation theory for a Legendre PWS has been given by Totenhofer et al, so we do not repeat this material here. Notice that the numerical values of f (θ R ) at a fixed θ R are independent of resummation.…”
Section: Nearside–farside Theorymentioning
confidence: 99%
“…The most recent review of NF theory is that of Child, while shorter (earlier) reviews can be found in refs . Recent applications of NF techniques have provided insights into the dynamics of the CH 4 + Cl → CH 3 + HCl reaction, the S N 2 Cl – + CH 3 Br → ClCH 3 + Br – reaction, four complex-mode reactions, rainbow scattering in reactive collisions, , and the forward-angle scattering of the H + HD → H 2 + D reaction …”
Section: Introductionmentioning
confidence: 99%